Social Responsibility and Local Sustainable Development in Relation to the Perception of Daily Life in the Public and Private Sectors - Hübel (Anghel), Ștefania-Rodica; Stan, Mari-Isabella; Tasențe, Tănase (Technium Social Sciences Journal, 2023)
This research investigates the intersection of social responsibility and local sustainable development in relation to the perception of daily life in the public and private sectors. It uses data from brandBerry SRL to explore participants' perceptions of their daily lives, their lives in relation to the pre-pandemic period, their future outlook, their income sufficiency, and their food procurement sources. The study uncovers intriguing differences between public and private sector employees, such as varying levels of job satisfaction, pandemic impact, and future uncertainty. However, statistical analyses suggest these differences are not always significant, indicating the need for further research. Interestingly, self-produced food represents a notable proportion of food sources, suggesting a potential trend towards sustainability. This study contributes to understanding how individuals in different sectors perceive their daily lives and future prospects, providing insights into social responsibility and sustainable local development.